INHIBISI NYERI DENGAN TRANCUTANEOUS ELECTRICAL STIMULATION PADA LANSIA DENGAN KONDISI PARKINSON - Mariel Daba (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
Abstract: Parkinson's is a progressive degenerative disease that causes motor dysfunction. Individuals with Parkinson's also experience non-motor symptoms such as pain. Pain is one of the most frequently reported debilitating symptoms among individuals with Parkinson's. TENS as a non-invasive and non-pharmacological treatment has been used to treat a variety of neuropathic pain. The analgesic effect of TENS has been shown to be achieved through neurobiological mechanisms that affect the peripheral nervous system and central nervous system. This study aims to determine the intensity of pain in individuals with Parkinson's against pain reduction by administering TENS to the superficial radial nerve. The method in this study was Quasi Experimental with a research design in the form of a pretest – posttest group design on the elderly Parkinson's at RSU Aulia, South Jakarta. In this study, the number of samples was 12 people who were divided into 2 groups, namely the control group and the treatment group, each group consisted of 6 people. The measuring instrument used was the VAS which was measured before and after TENS was given to each group. The results of the hypothesis test with the Unpaired T-Test showed a significant reduction in pain in the treatment group (by administering TENS) with p value = 0.00** (p <0.05). The conclusion in this study is that treatment with TENS administration of pain has an analgesic effect on the elderly Parkinson's.